Notes on dance composition through the 'test' bias (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article discusses how the so-called 'test bias' presents a compositional and investigative way of relating to the elaboration of movement in dance. To do this, some situations linked to the creation of the solo-study entitled Estudos sobre mover will be analyzed. From these, we dimension the production of movement in dance as a form of reasoning, delineating it as a logical proposition. Next, we discuss the investigative relationship that is proposed in the composition of movements, in which gestural possibilities are tested, qualifying a logical and characteristic way of composing dances. On this path, we are discussing more emphatically with C. S. Peirce’s Semiotic Logic.
Keywords: dance; movement; logic; investigation